2020
DOI: 10.1113/jp279152
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms underlying the stimulatory effect of inhaled sulfur dioxide on vagal bronchopulmonary C‐fibres

Abstract: Key points Brief inhalation of SO2 of concentration >500 p.p.m. triggered a pronounced stimulatory effect on vagal bronchopulmonary C‐fibres in anaesthetized rats. This stimulatory effect was drastically diminished by a pretreatment with NaHCO3 that raised the baseline arterial pH, suggesting a possible involvement of acidification of airway fluid and/or tissue generated by inhaled SO2. The stimulation was completely abolished by pretreatment with antagonists of both acid‐sensing ion channels and transient re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The role of SARs in cough production has been questioned recently based, in part, on the nonspecificity of sulfur dioxide ( Canning et al, 2006 ), which was employed in these previous studies to block SARs in the rabbit ( Hanáček et al, 1984 ; Sant’Ambrogio et al, 1984 ); sulfur dioxide can excite airway C-fibers ( Atzori et al, 1992 ; Lin et al, 2020 ; Wang et al, 1996 ). However, recent work by Poliacek and coworkers (2016) ( Poliacek et al, 2016 ) has shown that the cough motor pattern can be altered by out-of-phase inflations delivered by a custom mechanical ventilator in animals with intact chest walls.…”
Section: Introductionmentioning
confidence: 99%
“…The role of SARs in cough production has been questioned recently based, in part, on the nonspecificity of sulfur dioxide ( Canning et al, 2006 ), which was employed in these previous studies to block SARs in the rabbit ( Hanáček et al, 1984 ; Sant’Ambrogio et al, 1984 ); sulfur dioxide can excite airway C-fibers ( Atzori et al, 1992 ; Lin et al, 2020 ; Wang et al, 1996 ). However, recent work by Poliacek and coworkers (2016) ( Poliacek et al, 2016 ) has shown that the cough motor pattern can be altered by out-of-phase inflations delivered by a custom mechanical ventilator in animals with intact chest walls.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, the lag pattern between exposure and the risk of COPD admission was different for particulate and gaseous pollutants: gaseous pollutants increased the risk immediately after exposure, whereas particulate pollutants increased the risk gradually up to day 10. Gaseous pollutants, such as NO2 and SO2, might directly cause bronchoconstriction resulting in a COPD exacerbation [40,41]. The effects of PM on the airways may take longer to develop; they might include increased production of mucus in the airways, downregulation of expression of antimicrobial peptides leading to infectious exacerbations, and a proinflammatory environment induced by alveolar macrophages that clear PM [42].…”
Section: Discussionmentioning
confidence: 99%
“…Short-term exposures to SO 2 induce coughing and mucus secretion, acting mainly through afferent neurones and reflex bronchoconstriction, upregulation of vanilloid receptors and down-regulation of tight junctions. 89,90 High concentrations of SO 2 can cause inflammation of the respiratory tract, increase the risk of respiratory tract infections and increase all-cause mortality. [90][91][92][93][94][95]…”
Section: Short-term Exposure To So 2 and Asthma-related Outcomesmentioning
confidence: 99%